2009
DOI: 10.1097/aog.0b013e3181bea950
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer in Postmenopausal Women Using Estradiol–Progestin Therapy

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
29
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 40 publications
9
29
0
1
Order By: Relevance
“…A recent cohort study showed a lower risk of endometrial cancer through the use of continuous estrogen plus progestogen therapy compared with a sequential progestin regimen. 14 The findings were consistent with the results of the Million Women Study. 15 Furthermore, growing evidence has also suggested that the LNG-IUS is more effective than oral progestogen in the treatment of endometrial hyperplasia.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…A recent cohort study showed a lower risk of endometrial cancer through the use of continuous estrogen plus progestogen therapy compared with a sequential progestin regimen. 14 The findings were consistent with the results of the Million Women Study. 15 Furthermore, growing evidence has also suggested that the LNG-IUS is more effective than oral progestogen in the treatment of endometrial hyperplasia.…”
supporting
confidence: 87%
“…14,15 The use of continuous progestogen is associated with a lower risk of endometrial cancer than is the use of sequential progestogen. 14,15 Likewise, the most recent case control study also showed that the use of sequential and long-cycle estrogen-progestogen therapy was associated with an increased risk of endometrial cancer, whereas the use of continuous estrogen-progestogen therapy or estradiol plus LNG-IUS showed a decreased risk. 29 Another finding of this review is that the discontinuation rate tended to be lower in the ET plus LNG-IUS groups than in ET plus systemic progestogen groups.…”
Section: Summary Of Evidencementioning
confidence: 98%
“…11 Only 10% of Finnish breast cancer patients ultimately die of breast cancer 26 ; in our study, this mortality risk was blunted by the large reductions in the risks of CHD and stroke deaths. The use of continuous EPT was accompanied by a decrease (up to 80%) in the risk of uterine cancer, 27 which may have also contributed to the reduction of all-cause mortality in HT users in our study.…”
Section: Discussionmentioning
confidence: 89%
“…As a result of unopposed estrogen use, endometrial hyperplasia or cancer will occur in nearly half of women within 3 yr. Although either continuous or sequential progestin administration largely negates the increased risk as demonstrated in numerous trials including the WHI (23), long-term variations between progestin regimens have been recently described (24). Data from nearly 250,000 MHT users in Finland were extracted from a national registry.…”
Section: Endometrial Cancermentioning
confidence: 99%